Effect of grooved pin-fins in a rectangular channel on heat transfer augmentation and friction factor using Taguchi method. (November 2016) - Eren, M.; Caliskan, S.
Highlights: The averaged heat transfer from surfaces with T-GPFs is higher than that of C-GPFs. Enhancements in averaged Nusselt numbers over smooth surface are about 60.15%. The thermal performance factor of the T-GPFs is found to be the best and is about 2.81. Abstract: In this study, the effect of both cylindrical grooved pin-fins (C-GPFs) and triangular grooved pin-fins (T-GPFs) into the rectangular channel on heat transfer augmentation, Nusselt number and friction factor were experimentally investigated. In planning of the experiments, different Reynolds number, grooved distance rates (b/e), pin-fin geometry, array types and flow direction were chosen as the design parameters. Measurements were carried out according to these parameters. Air was used as the fluid. The grooved pin-fins were placed on the heating plate in in-line and staggered arrays and as vertical to the turbulent flow. Reynolds numbers and grooved distance rates (b/e) considered ranged from 3188 to 15, 146 and 1 to 3.446, respectively. The heat transfer results were obtained using the infrared thermal imaging technique. For each of pin-fin geometry, the data were obtained for the effect of the heat transfer and pressure drop, Nusselt number as a function of Reynolds number, friction factor and thermal performance factor. Moreover, in this study, effort was made to determine the optimum values of the design parameters within the system of grooved pin-fins by using the Taguchi method, and the orthogonal experimental plan of L16 (4 2 × 2 3 ) was chosen. Nusselt number, friction factor and the thermal augmentation factor were considered as performance characteristics at the Taguchi method. Heat transfer rates of C-GPFs and T-GPFs were compared with those of a smooth channel. In addition, local and averaged Nusselt number were presented and total heat transfer improvement was studied. As a result, the best heat transfer augmentation was obtained with the T-GPFs.